THE EFFECT OF MSMES AND MANPOWER ON ECONOMIC GROWTH OF TUBAN DISTRICT - Khotimah, Siti Khusnul; Surhatono, Edy (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTMSMEs currently have a very large role in the national economy or regional economy. MSMEs are the largest contributor to national GDP. In implication, MSMEs can absorb a lot of labor with a population that has low education. The workforce referred to in this study is the number of workers from the MSME. In the economic growth of a region, MSMEs and the number of workers have a very large contribution. This study aims to determine whether the number of MSMEs or the number of MSME workers has more influence on economic growth in the Tuban area, seen from the number of industrial industries that have begun to spread in the area. This research is a descriptive research with a quantitative approach. . Researchers used secondary data in the form of a ten-year time series, namely 2011-2020, sourced from the Tuban BPS (Central Statistics Agency) and the Tuban Cooperative and MSME Office. The method used in this study is multiple linear regression with the OLS method. The results of this study simultaneously the number of MSME units and the number of MSME workers have an effect on GRDP or economic growth in Tuban Regency. . This study uses the independent variables the number of MSME units and the number of MSME workers while the dependent variable is economic growth.Keywords: MSMEs; Labor; Economic Growth